Czy zbiór polskich frazeologizmów pochodzenia biblijnego jest zbiorem zamkniętym? - Koziara, Stanisław (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2019)
The paper is dedicated to some selected units of biblical origin in the Polish language, namely fixed word combinations (idiomatic expressions). The author is trying to answer the question whether the collection of such units has the qualities of a closed set, or demonstrates a contemporary tendency to multiply its resources. What is essential for this description is the division into primary and secondary units of biblical origin. Apart from historical data and conditions, which are linked with this issue of Polish phraseology, the paper also contains several examples of the processes, as a result of which the language acquired new phrases of biblical origin.